An Alarming Increase in Blood Triglyceride Levels for Community Health Reflects Protective Protein Defects - Onat, Altan; Hergenc, Gulay; Can, Gunay; Yuksel, Husniye; Ugur, Murat; Kaya, Hasan (ORTADOGU AD PRES & PUBL CO, 2010)
Objective: To investigate whether the increase in tryglyceride levels of our adult population detected formerly was continuing in previous ten years according to data of TEKHARF study cohort. Material and Methods: Fasting plasma trygliceride levels of 2862 participants (mean age 54 years, range between 47-63) were evaluated according to sex and age groups. Tryglyceride levels were measured with enzymatic assays; both original values and logarithmic transformational values were used for analysis. Age standardization was conducted for mean values of age group 30-79 years according to age group intensities of country population. Additionally, ultimate tryglyceride values of 2294 participants were compared to the values 7.8 +/- 2.3 years previously. The correction of mean tryglyceride levels (-2,6 mg/dl for females and +9,8 mg/dl for males) was conducted according to the prediction of an increase related to aging. Results: Triglyceride levels increased to 152.3 mg/dl in males and 135.6 mg/dl in females, -adjusting for age- with an increase of +18.7 mg/dl since 1998. Mean values reached to 177 mg/dl in males and 154 mg/dl for females. Triglyceride levels of participants from urban areas were found to be 7 mg/dl higher compared to the levels of participants from rural areas (p = 0.009). Mean triglyceride levels were found to increase of 25 mg/dl and 20 mg/dl in males and females respectively -after age standardization had been conducted - when compared to screening data of year 1990. Increasing trend was higher in recent period. Conclusion: Triglyceride levels of Turkish adults which was between normal values has been increasing 1 mg/dl and more yearly for both genders after adjusted for age and the rate of this increase appeared to be accelerated in last ten years. This trend is the major indicator underlying the defect of protective proteins setting off the proinflammatory condition/oxidative stress. We conclude that it is the time to campaign in order to reverse this worrisome condition for our community health.
Keywords: Epidemiology; risk factors; triglycerides; HIGH-DENSITY-LIPOPROTEIN; CARDIOVASCULAR-DISEASE; METABOLIC SYNDROME; RISK-FACTORS; PLASMA; MUTATION; LIPIDS; TURKS; HDL; General & Internal Medicine